2011
DOI: 10.1007/s11547-011-0678-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the need for computed tomography for lower-third-molar extraction: a survey among 322 dentists

Abstract: Our survey revealed a cautious approach among the professionals interviewed, who tended to overprescribe CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…When the similar studies are considered the response rates of web surveys changes between 4.00% and 21.5%, Russell et al reported the response rate of 4.00%, Swetz et al reported the response rate of 4.00%, Kim et al reported the response rate of 9.00%, Ocakoglu et al reported the response rate of 9.10%, Sivolella et al reported the response rate of 11.80% and Sax et al reported the response rate of 21.50, therefore the response rate of our study is acceptable (16.62%). [13][14][15][16][17][18] The low response rate is not surprising given that response rates to surveys have declined dramatically over time due to the proliferation of junk mail, the rapid growth and ease of large-scale surveys, and resulting complaints that people feel "bombarded" with Internet-based surveys despite increasing demands on their time. 19…”
Section: Discussionmentioning
confidence: 99%
“…When the similar studies are considered the response rates of web surveys changes between 4.00% and 21.5%, Russell et al reported the response rate of 4.00%, Swetz et al reported the response rate of 4.00%, Kim et al reported the response rate of 9.00%, Ocakoglu et al reported the response rate of 9.10%, Sivolella et al reported the response rate of 11.80% and Sax et al reported the response rate of 21.50, therefore the response rate of our study is acceptable (16.62%). [13][14][15][16][17][18] The low response rate is not surprising given that response rates to surveys have declined dramatically over time due to the proliferation of junk mail, the rapid growth and ease of large-scale surveys, and resulting complaints that people feel "bombarded" with Internet-based surveys despite increasing demands on their time. 19…”
Section: Discussionmentioning
confidence: 99%
“…Because of large variation in inferior alveolar nerve/third molar relationships, a detailed preoperative radiographic assessment is required to identify both the position (buccal, lingual or inferior) and approximation of the mandibular canal (MC) to the third molar to minimise the risk of postoperative dysaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assumed that most clinicians use panoramic radiographs with a series of radiological criteria as an indicator of the relationship, and thus the risk, of postoperative dysaesthesia. In a Web‐based survey of 2,713 Italian dentists (11.9% of answers) concluded that recommendations for CT were proportional to the number of radiographic signs indicating a risk of inferior alveolar nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing acquisition and use of 3D radiographic imaging within dentistry (e.g., for implant treatment planning [ 18 ] and preoperative assessment of MTM [ 19 , 20 ]) is raising the overall ionizing radiation exposure of the population, i.e., an additional increase of the cancer incidence of 0.46 per year was estimated due to applying CBCT imaging prior to MTM removal [ 21 ]. Therefore, MRI could be a reasonable alternative for the planning of various surgical procedures within dentistry [ 22 ].…”
Section: Introductionmentioning
confidence: 99%